COMPARATIVE ANALYSIS OF ULTRASOUND AND MAGNETIC RESONANCE IMAGINNG FOR THE EARLY DETECTION OF CRYPTORCHIDISM IN CHILDREN AND ITS CORRELATION WITH ORCHIDOPEXY FINDINGS - Pashoska Vasileska, Milkica; Nikolova, Sonja; Stefanovska, Vesna Velikj; Stojovska Jovanovska, Elizabeta; Jakimovska Dimitrovska, Maja; Dimitrijevikj, Kristina (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
This study aimed to investigate the diagnostic accuracy of ultrasound (US) and magnetic resonance imaging (MRI) in detecting cryptorchidism in pediatric patients and to compare these imaging modalities with classic orchidopexy findings. Conducted between 2018 and 2019 at the PHI University Institute of Radiology - Skopje in collaboration with the PHI Clinic for Children's Surgery at the Mother Teresa University Clinical Centre - Skopje, this cross-sectional study included pediatric patients up to 14 years old with suspected cryptorchidism. B-mode ultrasound and MRI, including DW-MRI sequences, were employed for localization of undescended testes. These imaging findings were compared with those obtained from classic orchidopexy, serving as the gold standard. A total of 41 male pediatric patients (â‰¤14 years old) with suspected cryptorchidism were enrolled, with a mean age of 6.76Â±3.74 years. MRI demonstrated superior detection and visualization of undescended testes compared to ultrasound. Specifically, MRI significantly improved the preoperative diagnostic accuracy, especially in localizing non-palpable undescended testes, when compared to ultrasound. The findings suggest that MRI is more effective than ultrasound in detecting undescended testes in pediatric patients. Furthermore, MRI enhances the preoperative diagnostic accuracy, particularly in localizing non-palpable undescended testes, thereby potentially serving as a recommended imaging modality for this purpose. Keywords: Cryptorchidism, Ultrasound, Magnetic Resonance Imaging, Diagnostic Accuracy, Orchidopexy, Pediatric Radiology.